Studying the Consumption Behaviour of Generations Y and Z towards Ready-To-Drink Coffee - Hurdawaty, Ramon; Wibowo, FX Setiyo; Sulistiyowaty, Reni (The Postgraduate School of Tourism Sahid Polytechnic, 2023)
Purpose: This study aims to explore consumption behavior both Gen Y and Gen Z towards ready-to-drink coffee in Indonesia. Research methods: This study is a survey research with quantitative method. The survey was conducted on 200 respondents employing online media by delivering electronic questionnaire consisting of 16 questions related to coffee consumption behavior and 6 demographic questions. Results and discussion : Generations Y and Z like cold brewed coffee, prefer to drink coffee at coffee shops while socializing, buy coffee with the highest price range of IDR 20,000-29,000, often use delivery service by ordering through the app. Implication: it is appropriate for coffee shop owners to carry out a marketing mix (4P) i.e. product, promotion, price and place (distribution mix) with reference to the consumption behavior of coffee from them, so that the sustainability of the ready-to-drink coffee business can be achieved. Keywords: generations Y and Z, ready-to-drink coffee, consumption behavior